Robust and Reproducible Agrobacterium-Mediated Transformation System of the C4 Genetic Model Species Setaria viridis - Nguyen, Duc Quan; Van Eck, Joyce; Eamens, Andrew L.; Grof, Christopher P. L. (Frontiers in Plant Science, 2020)
Setaria viridis (green foxtail) has been identified as a potential experimental model system to genetically and molecularly characterise the C4 monocotyledonous grasses due to its small physical size, short generation time and prolific seed production, together with a sequenced and annotated genome. Setaria viridis is the wild ancestor of the cropping species, foxtail millet (Setaria italica), with both Setaria species sharing a close evolutionary relationship with the agronomically important species, maize, sorghum and sugarcane, as well as the bioenergy feedstocks, switchgrass and Miscanthus. However, an efficient and reproducible transformation protocol is required to further advance the use of S. viridis to study the molecular genetics of C4 monocotyledonous grasses. An efficient and reproducible protocol was established for Agrobacterium tumefaciens-mediated transformation of S. viridis (Accession A10) regenerable callus material derived from mature seeds, a protocol that returned an average transformation efficiency of 6.3%. The efficiency of this protocol was the result of the: (i) use of mature embryo derived callus material; (ii) age of the seed used to induce callus formation; (iii) composition of the callus induction media, including the addition of the ethylene inhibitor, silver nitrate; (iv) use of a co-cultivation approach, and; (v) concentration of the selective agent. Our protocol furthers the use of S. viridis as an experimental model system to study the molecular genetics of C4 monocotyledonous grasses for the potential future development of improved C4 cropping species.